Emergent phenomena in scientific publishing: A simulation exercise - Jakob Kapeller; Stefan Steinerberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
We model the academic production process understood as the creation, submission, evaluation and publication of papers: scientists produce manuscripts to the best of their abilities and try to publish them in academic journals, which rely on referees to judge the submissions. The resulting model is able to reproduce several properties of the journal-landscape but also illustrates that even under unrealistically optimistic assumptions the process of scientific publishing will give rise to several universal emergent phenomena for purely mathematical reasons: the efficiency of scientific publishing is delicate and very unstable.
Keywords: 330; Citation metrics; simulation; reviewing; manuscript quality; submission behavior